2019
DOI: 10.1101/gr.240093.118
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of epigenome and transcriptome landscapes with aging in mice reveals widespread induction of inflammatory responses

Abstract: Aging is accompanied by the functional decline of tissues. However, a systematic study of epigenomic and transcriptomic changes across tissues during aging is missing. Here, we generated chromatin maps and transcriptomes from four tissues and one cell type from young, middle-aged, and old mice-yielding 143 high-quality data sets. We focused on chromatin marks linked to gene expression regulation and cell identity: histone H3 trimethylation at lysine 4 (H3K4me3), a mark enriched at promoters, and histone H3 ace… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
217
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(245 citation statements)
references
References 83 publications
(134 reference statements)
25
217
1
2
Order By: Relevance
“…heart, liver, cerebellum, olfactory bulb) and one primary cell type (i.e. primary neural stem cell cultures [NSCs]) at 3 ages throughout mouse lifespan (3, 12 and 29 months of age [22]. Although we do not find evidence for large changes in histone H3 expression levels or nucleosome occupancy across ages, we do identify reproducibly remodeled nucleosomes with mouse aging.…”
Section: Introductioncontrasting
confidence: 66%
“…heart, liver, cerebellum, olfactory bulb) and one primary cell type (i.e. primary neural stem cell cultures [NSCs]) at 3 ages throughout mouse lifespan (3, 12 and 29 months of age [22]. Although we do not find evidence for large changes in histone H3 expression levels or nucleosome occupancy across ages, we do identify reproducibly remodeled nucleosomes with mouse aging.…”
Section: Introductioncontrasting
confidence: 66%
“…First, we analyzed factors that may sensitize aged brain to greater stroke damage during normal aging process. A number of studies has documented that inflammation is increased in the aged brain [105][106][107] , and it has been reported that the changes occur predominantly in glial cells 108,109 . Our results are well in line with these reports as we detected upregulation of a number of pro-inflammatory genes (Figures 1A, S1A) that map to signatures of aged and reactive glial cells, including the signature of a recently identified subpopulation of Ccl4+ pro-inflammatory microglia 60,61 (Figures 1B, S2).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression and other types of “omics” data have been widely used to study the process of aging (Edwards et al, ; Peters et al, ). For examples, epigenome and transcriptome landscapes with aging in mice have revealed widespread induction of inflammatory responses (Benayoun et al, ); likewise, the downregulation of mitochondrial genes across human tissues has been consistently reported (Glass et al, ; Yang et al, ). Studying transcriptomes across multiple species with varied lifespans has similarly reveled a potential role for gene expression regulation in contributing to longer lifespans (S. Ma et al, ).…”
Section: Introductionmentioning
confidence: 99%